ANALISIS POMPA IRIGASI TENAGA SURYA UNTUK MEMENUHI KEBUTUHAN AIR IRIGASI PADA SAWAH TADAH HUJAN DI NAGARI PADANG GALUNDI KABUPATEN SOLOK - Maizir, Maizir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In Nigari Padang Galundi there are rice fields with an area of approximately 36 hectares already have an irrigation network system, but it has not been functioning for a long time. Currently, rice fields can only be planted with rice crops during the rainy season, or called rainfed rice fields. The water source from Batang Sumani uses a water pump that has not functioned for a long time, this is because the community is unable to provide the operating costs. To overcome the lack of irrigation water, it is planned to procure solar irrigation pumps. From the results of the analysis of the water demand in the fields, the maximum water demand in the fields is 1.43. lt/sec/ha. For an irrigation area of 36 ha, the irrigation water requirement for DI Padang Galundi is 60.56 liters/second. To meet the water needs, a solar irrigation pump of 2.5 HP or 1800 watts is needed. Furthermore, 18 units of solar panel modules are needed to produce 1800 watts of power.